2018
DOI: 10.5117/tvgn2018.2.brin
|View full text |Cite
|
Sign up to set email alerts
|

De zevenkoppige draak van ongelijkheid

Abstract: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the work. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In general, studies on organizational inclusion have been limited by an inward orientation on single employers and individual perceptions of employees, failing to capture the complexity or organizational embeddedness in a wider national and sector/industry context (Dobusch, 2014; van den Brink, 2017). While Shore et al (2018) do not explicitly address the relationship between the organization and its environment in their inclusion themes, other scholars do engage with this issue.…”
Section: Concepts Of Organizational Inclusion and Low-wage Labor: Idementioning
confidence: 99%
“…In general, studies on organizational inclusion have been limited by an inward orientation on single employers and individual perceptions of employees, failing to capture the complexity or organizational embeddedness in a wider national and sector/industry context (Dobusch, 2014; van den Brink, 2017). While Shore et al (2018) do not explicitly address the relationship between the organization and its environment in their inclusion themes, other scholars do engage with this issue.…”
Section: Concepts Of Organizational Inclusion and Low-wage Labor: Idementioning
confidence: 99%
“…This research shows that progress is vulnerable and internal and external pressures, for instance, the financial crisis or mergers, can throw progression back. Although a process-based view on change is common in the field of (critical) diversity management (Janssens and Steyaert, 2019), we often hold a linear view in terms of outcomes (van den Brink, 2018). This study showed that organizational learning is a continuous and iterative process in which an environment is created in which organization members can learn, reflect and experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous initiatives aiming to transform organizations into more equal, inclusive and diverse work places, progress remains À at bestslow (Dobbin and Kalev, 2016;Evans, 2014). Diversity practices rarely translate into deep systemic change (Acker, 2006;Leenders et al, 2019), as interventions often stay superficial (Ahmed, 2007;Eriksson-Zetterquist and Styhre, 2008), geared toward fixing women/minorities (Ely and Meyerson, 2000;Zanoni et al, 2010) and are implemented rather ad hoc (Benschop et al, 2015;van den Brink, 2018) or even become counterproductive (Romani et al, 2019). In addition, planned diversity interventions barely lead to sustainable change in the long run as it is difficult to change norms and daily practices of organizational members (Eriksson-Zetterquist and Renemark, 2016;Acker, 2000).…”
Section: Introductionmentioning
confidence: 99%